Pengaruh Perceptual-Motor Training terhadap Perubahan Kemampuan Koordinasi Mata, Tangan dan Kaki Anak Tunagrahita di SLB Pematangsiantar - Fujastawan, I Ngurah Gede Verar; Ginting, Isaharpika Br; Herawati, Noni; Ritonga, Rizky Randa (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2024)
Background: Children with intellectual disabilities are children who have a lower intellectual level than normal children in their age, it causes intellectual disability children poor in child’s development that effect cognitive, motoric skill, social, and emotions. Mild intellectual disabilities are the largest population of various categories of intellectual disabilities. This study aims to determine the effect of Perceptual-Motor Training on eye, hand, and foot coordination skill of intellectual disability children in SLB Pematangsiantar. Method: This study uses a quasi-experimental design with the type of one group pretest and posttest. The subject of this study were mild intellectual disability children in aged 10-14 years old and able to communicate. The number of respondents was 17 children and attend Perceptual-Motor Training for 12 treatments in 4 weeks. Result: The results of this study after Shapiro Wilk normality test obtained normal distribution data (p >0.05), then carried out hypothesis testing using Paired T - Test and obtained a significant value p < 0.001 (p <0.05). The data analysis from pretest and post test showed that all respondent has an increase on motor coordination. Conclusion: Perceptual-Motor Training have a significant effect to improve eye, hand, and foot coordination skill of intellectual disabilities children in SLB Pematangsiantar.